Superconductivity in the superhard boride WB4.2. (27th September 2018) - Carnicom, Elizabeth M; Strychalska-Nowak, Judyta; Wiśniewski, P; Kaczorowski, D; Xie, W; Klimczuk, T; Cava, R J
Abstract: We show that the superhard boride WB4.2 is a superconductor with a Tc of 2.05(5) K. Temperature-dependent magnetic susceptibility, electrical resistivity, and specific heat measurements were used to characterize the superconducting transition. The Sommerfeld constant γ for WB4.2 is 2.07(3) mJ mol −1 K −2 and the Δ C / γ Tc  = 1.56, which is somewhat higher than what is expected for weakly coupled Bardeen–Cooper–Schrieffer type superconductors. The H c 2 versus T plot is linear over a wide temperature range but does show signs of flattening by the lowest temperatures studied and therefore the zero temperature upper critical field ( μ 0 H c 2 (0)) for WB4.2 lies somewhere between the linear extrapolation of μ 0 H c 2 ( T ) to 0 K and expectations based on the Werthamer–Helfand–Hohenberg model.